2015
DOI: 10.3174/ajnr.a4336
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Flow-Diverter Endothelialization and Thrombus Organization in Giant Fusiform Aneurysms after Flow Diversion: A Histopathologic Study

Abstract: BACKGROUND AND PURPOSE:Treatment of giant fusiform aneurysms with flow diverters has been associated with a relatively high rate of complications. Our goal was to study the evolution of flow-diverter endothelialization and thrombus organization at different time points after flow-diverter treatment in giant fusiform aneurysms to better understand reasons for flow-diverter thrombosis and delayed aneurysm ruptures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 29 publications
3
46
0
3
Order By: Relevance
“…22 It is thought that poor wall apposition can result in delayed endothelialization of the stent, resulting in an increased risk of instent thrombosis in the delayed postoperative period. 20,21 This is supported by the fact that the fusiform aneurysms that were associated with stroke in our series were generally large or giant, with a mean aneurysm size of nearly 25 mm and a mean neck size of 26 mm. The large aneurysm maximum diameter and neck size likely made achieving good wall apposition, thus increasing the risk of in-stent thrombosis.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…22 It is thought that poor wall apposition can result in delayed endothelialization of the stent, resulting in an increased risk of instent thrombosis in the delayed postoperative period. 20,21 This is supported by the fact that the fusiform aneurysms that were associated with stroke in our series were generally large or giant, with a mean aneurysm size of nearly 25 mm and a mean neck size of 26 mm. The large aneurysm maximum diameter and neck size likely made achieving good wall apposition, thus increasing the risk of in-stent thrombosis.…”
Section: Discussionsupporting
confidence: 54%
“…A number of studies have reported poor outcomes and high rates of thrombosis in the treatment of dolichoectatic and fusiform aneurysms, particularly of the posterior circulation, with flow diverters in general. 9,20,21 High rates of infarction seen in these patients are likely due to a combination of poor wall apposition due to the large size of the aneurysm, early discontinuation of antiplatelet therapy, and the requirement for multiple PEDs. 20,21 Recently, there has been increased interest in the relationship between wall apposition of the flow diverter and rates of delayed postoperative stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various articles have suggested that this aneurysmal remnant may be biologically active, [4][5][6] however, most of these address early rupture rather than delayed recanalization. Our case is unusual and unique as reopening of the previously 'thrombosed' aneurysmal remnant has, to our knowledge, not previously been documented in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Anevrizma boynuna yerleştirilen akım yönlen-dirici stent, akımı parent artere yönlendirerek anevrizma içerisinde akımın yavaşlamasını ve trombozunu sağlar [19,20]. Endovasküler koil embolizasyon aksine akım yönlendirici stent ile tedavi edilen bir anevrizmanın tromboze olması 6-12 aylık süreye yayılmaktadır (Resim 11, 12) [20]. Aslında akım yönlendirici stentler, çok sık örgü yapısına sahip metal kafeslerdir ve stent duvarında diğer stentlere oranla daha fazla metal tel, çok daha az sayıda gözenek bulunmaktadır.…”
Section: Akım Yönlendirici Stentunclassified